High Performance Flexible Nonvolatile Memory Based on Vertical Organic Thin Film Transistor. (6th September 2017) - Hu, Daobing; Wang, Xiumei; Chen, Huipeng; Guo, Tailiang
Abstract: Flexible floating‐gate organic transistor memory (FGOTM) is a potential candidate for emerging memory technologies. Unfortunately, conventional planar FGOTM suffers from weak driving ability and insufficient mechanical flexibility, which limits its commercial application. In this work, a novel flexible vertical FGOTM (VFGOTM) is reported. Benefitting from new vertical architecture, VFGOTM provides ultrashort channel length to afford an extremely high current density. Meanwhile, VFGOTM devices exhibit excellent memory performance and outstanding retention property. The memory properties of VFGOTM devices are comparable or even better than traditional planar FGOTM and much better than the reported organic nonvolatile memory with vertical transistor structures. More importantly, organic nonvolatile memory with vertical transistor structures is investigated for the first time on a flexible substrate. The results show that VFGOTM architecture allows vertical current flow across the channel layer to effectively eliminate the effect of mechanical bending during current transport, which significantly improves the mechanical stability of the flexible VFGOTM. Hence, with a combination of excellent driving ability, memory performance, and mechanical stability, VFGOTM devices meet the practical requirements for high performance memory applications, which have great potential for the application in a wide range of flexible and wearable electronics. Abstract : A novel vertical‐architecture, floating‐gate organic transistor memory fabricated on a flexible substrate is reported. The unique vertical architecture enables memory devices with ultrashort channel length, which provides a large current density (excellent driving ability), fast operation, and mechanical stability, showing great potential for the application in a wide range of flexible and wearable electronic applications.